2021
DOI: 10.3389/fnagi.2021.766311
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Delivered Cognitive Training and Transcranial Direct Current Stimulation in Patients With HIV-Associated Neurocognitive Disorder: A Randomized Trial

Abstract: Objective: HIV infection is associated with impaired cognition, and as individuals grow older, they may also experience age-related changes in mental abilities. Previous studies have shown that computer-based cognitive training (CCT) and transcranial direct current stimulation (tDCS) may be useful in improving cognition in older persons. This study evaluated the acceptability of CCT and tDCS to older adults with HIV-associated neurocognitive disorder, and assessed their impact on reaction time, attention, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 103 publications
0
24
0
Order By: Relevance
“…To the best of our knowledge, there are six published works that investigated the safety and efficacy of tDCS in PWH. One open-label study examined the effects of tDCS in treating depression in PWH [ 11 ], and five single-blind studies investigated whether a combination of tDCS and cognitive training could improve cognitive performance in PWH [ 12 16 ]. In two studies with PWH participants who were older than 50 and met the Frascati criteria for HAND diagnosis, Ownby and colleagues investigated the effects of anodal tDCS over the left dorsal lateral prefrontal cortex (DLPFC) while participants were receiving a computer-based cognitive training [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are six published works that investigated the safety and efficacy of tDCS in PWH. One open-label study examined the effects of tDCS in treating depression in PWH [ 11 ], and five single-blind studies investigated whether a combination of tDCS and cognitive training could improve cognitive performance in PWH [ 12 16 ]. In two studies with PWH participants who were older than 50 and met the Frascati criteria for HAND diagnosis, Ownby and colleagues investigated the effects of anodal tDCS over the left dorsal lateral prefrontal cortex (DLPFC) while participants were receiving a computer-based cognitive training [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subjectively, PWH who received active tDCS tended to rate the intervention trials more positively. However, objective neuropsychological tests did not find any significant difference between active and sham tDCS [ 12 , 16 ]. In a series of tDCS studies combined with speed of processing training, Cody, Fazeli, Pope, Vance, and colleagues investigated the effects of anodal tDCS over the right DLPFC in older PWH (aged 50 and older) and age-matched HIV-uninfected controls: compared to sham tDCS, active tDCS led to a stronger improvement in psychomotor speed [ 15 ], cautious driving behavior [ 13 ], and oral reading [ 14 ] in both HIV-infected and HIV-uninfected adults.…”
Section: Introductionmentioning
confidence: 99%
“…In the other studies, a monopolar montage was utilized, where one electrode was placed on the scalp, and the other was positioned extracerebrally, such as on the arm. The studies [43][44][45][46][47][48] found were published between 2012 and 2022. Among the included studies, three adopted parallel designs, and one adopted a crossover design.…”
Section: Resultsmentioning
confidence: 99%
“…30 Another computer-delivered cognitive training randomized controlled trial (RCT) found 25.4% (14/55) of participants receiving a Mild Neurocognitive Disorder HAND diagnosis chose not to continue with randomization. 35 While these studies do not report reasons for post-screening, pre-randomization attrition beyond participants choosing not to participate, these dropoff rates are higher than the 5%–10% post-screening, pre-randomization attrition rate frequently reported in psychosocial clinical trials that employ a brief screen for cognitive impairment in the general population. 36 We contend that the brief screen has strong potential to facilitate participant recruitment, enrollment, and randomization (and ameliorate attrition rates) for clinical trials focused on psychosocially remediating cognitive impairment among people living with HIV, as the brief screen can mitigate the barrier of intensive testing for individuals who may not have the motivation or capacity to undergo complex testing.…”
Section: Implications For Clinical Trialsmentioning
confidence: 97%
“…In the literature, we noted that several clinical trials focused on HAND reported significant rates of pre-intervention attrition. [30][31][32][33][34][35] One clinical trial testing cognitive rehabilitation therapy in people living with HIV found that 49.6% (59/119) who met the criteria for HAND then declined to be randomized into the trial. 30 Another computer-delivered cognitive training randomized controlled trial (RCT) found 25.4% (14/55) of participants receiving a Mild Neurocognitive Disorder HAND diagnosis chose not to continue with randomization.…”
Section: Implications For Clinical Trialsmentioning
confidence: 99%